Description of the puparium of Hermetia pulchra (Diptera: Stratiomyidae) from Brazil - Pujol-Luz, José Roberto; Godoi, Fabio Siqueira Pitaluga De; Barros-Cordeiro, Karine Brenda (Zootaxa, 2016)
The puparium of Hermetia pulchra is described, based on a single specimen reared in laboratory under controlled conditions until the emergence of an adult female. The puparium of H. pulchra was compared with puparium of H. illucens and some differential features were indicated. A checklist of the Brazilian species of the genus Hermetia is included, with new distributional records for H. pulchra in the Brazilian States of Bahia and Distrito Federal. Hermetia sphecodes is recorded for the first time for Brazil (State of Amazonas).